2007
DOI: 10.1002/mus.20937
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, placebo‐controlled, double‐blind pilot trial of ramipril in McArdle's disease

Abstract: McArdle's disease causes limitation in exercise capacity as well as disability, the severity of which has been associated with the angiotensin-converting enzyme (ACE) insertion (I)/deletion (D) haplotype-patients with the genotype associated with higher ACE activity show the most severe phenotype. Modulation of ACE activity through the use of inhibitors may thus positively affect disease expression. In a double-blind, randomized, placebo-controlled trial, we assessed the efficacy of an ACE inhibitor (2.5 mg ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…The ten patients studied include eight described in a recent randomized controlled trial of the ACE inhibitor ramipril in McArdle's disease (Martinuzzi et al 2007): each of those eight patients had three 31 P MRS studies, one pre-treatment (which is the only one used in the present, much more detailed analysis) and one at the end of each of two phases of a crossover study of ramipril vs placebo.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ten patients studied include eight described in a recent randomized controlled trial of the ACE inhibitor ramipril in McArdle's disease (Martinuzzi et al 2007): each of those eight patients had three 31 P MRS studies, one pre-treatment (which is the only one used in the present, much more detailed analysis) and one at the end of each of two phases of a crossover study of ramipril vs placebo.…”
Section: Methodsmentioning
confidence: 99%
“…As described elsewhere (Martinuzzi et al 2007), subjects lay supine with a 6 cm surface coil centred on the maximum circumference of the right calf muscle. Spectra were acquired with TR = 5 s at rest (128 FIDs), during aerobic incremental plantar flexion exercise (10% lean body mass for 2 min, then increasing 5% lean body mass per minute) to the latest point which subjects reported they could tolerate without loss of force, then post-exercise recovery (64 FIDs, time resolution of 10 s, results averaged in pairs of spectra, thus halving apparent time resolution, to increase signal/noise).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests that the variability in the phenotypic manifestation of McArdle disease in female patients is associated with the angiotensin-converting enzyme insertion (I)/deletion (D) halotypes. 104 Patients with the most severe phenotype (D/D genotype) have higher levels of angiotensin-converting 105 A recently conducted open-label study in 19 infants with Pompe disease showed that survival was significantly enhanced with recombinant human alglucosidase treatment (Myozyme, 20 and 40 mg/kg every 2 weeks). 106 In general, we are still lacking effective pharmacological therapy to prevent myopathy from developing and progressing.…”
Section: Treatmentmentioning
confidence: 98%
“…There is little evidence for benefit of creatine in other metabolic myopathies [46]. Angiotensin-converting enzyme (ACE) genotype is associated with disease severity in McArdle disease and, interestingly, a randomised study [47] of ramipril in eight patients showed possible benefit in those with the deletion/deletion ACE genotype. Exercise programmes of moderate intensity are beneficial in McArdle disease and mitochondrial disorders and may be helpful in other metabolic myopathies [48][49][50].…”
Section: Treatmentmentioning
confidence: 98%